Program Hipotetik Pribadi Sosial dalam Meningkatkan Kecerdasan Moral Siswa - Fitraturrohmah Fitraturrohmah; Siti Muhibah; Alfiandy Warih Wandoyo (Journal of Education and Counseling (JECO), 2020)
The dilatorial research was supported by the problem of moral class XI students at SMAN 5 Kota Serang. This can be proven from the results of the student needs questionnaire (AKPD) with a result of 42%. This study aims to determine the description and program design in overcoming the moral intelligence of class XI students at SMAN 5 Kota Serang. This type of research is descriptive research. The sampling technique used saturated samples or total sampling, which involved the entire population as research respondents with a total of 483 students. This research concerns the level of students' moral intelligence which can be seen through the following seven indicators of moral intelligence: 1) Empathy, 2) Respect, 3) Tolerance, 4) Conscience, 5) Self-control, 6) Kindness, 7) Justice . The data collection technique used is using a questionnaire / questionnaire instrument, and interviews. The data analysis technique used is descriptive quantitative. The results showed that the level of moral intelligence of class XI students at SMAN 5 Serang City can be seen from three categories, namely low with a total of 81 students with a percentage of 17%, a moderate category with 321 students with a percentage of 66%, and a high category with a total of 81 students. with a percentage of 17%. After knowing the level of moral intelligence of class XI students at SMAN 5 Serang City, a hypothetical program can be made or a social personal guidance program design based on the results obtained. Guidance and counseling services that can be carried out for the low category can be used group counseling services, for the medium category services that can be used are classical guidance services, and the last category for high, services that can be used are group guidance.